Controlling political communication in the blogosphere: business as usual in Malaysia - Shuaib, Farid Sufian (Bloomsbury Professional Ltd, 2011)
Malaysia has a list of restrictive laws that prevent the publication of political communications. Most of these laws were enacted before the explosion of online communications through online news portal and blogs. Malaysia, her citizens and her government have embraced this information communication technology in the belief of its ability to propel her to become a developed nation. Because of this conviction, the government guarantees that there will be no censorship of the internet. This guarantee invites the expectation that online communications will not suffer the same restrictions currently meted out to the press and broadcasters in Malaysia. The objective of this paper is to examine whether this expectation has materialised and assess to what extent the guarantee assists in the liberalisation of political communication through online publications in Malaysia by analysing relevant legal provisions, case reports and incidents.